2018
DOI: 10.2135/cropsci2017.09.0542
|View full text |Cite
|
Sign up to set email alerts
|

Annual and Perennial Peanut Mixed with ‘Pensacola’ Bahiagrass in North Florida

Abstract: Fertilization of perennial grass pastures is a major expense in beef cattle operations, and grass pastures may degrade in the absence of N fertilization. Grass–legume mixtures can reduce the demand for N fertilizer use while increasing productivity of the system. Arachis spp. have shown potential for use in association with grasses in the southeastern United States. During 2014, 2015, and 2016, we evaluated one annual peanut species (Arachis hypogaea L. TUFRunner ‘727’) and two perennial peanut species, pintoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 44 publications
(58 reference statements)
2
31
1
Order By: Relevance
“…In the early season, bahiagrass had generally greater participation in the BC; in the middle season, RP had greater contribution in the stand. In agreement with results of low performance of Florigraze RP associated with bahiagrass found by Dunavin (1992), Jaramillo et al (2018) reported that Florigraze had a slower establishment rate than Ecoturf. There are few studies evaluating RP and bahiagrass mixtures in terms of sward composition; among them, Dunavin (1992) and Jaramillo et al (2018) performed trials in Florida and evaluated the sward responses for 8 and 3 yr, respectively.…”
Section: Botanical Compositionsupporting
confidence: 90%
See 4 more Smart Citations
“…In the early season, bahiagrass had generally greater participation in the BC; in the middle season, RP had greater contribution in the stand. In agreement with results of low performance of Florigraze RP associated with bahiagrass found by Dunavin (1992), Jaramillo et al (2018) reported that Florigraze had a slower establishment rate than Ecoturf. There are few studies evaluating RP and bahiagrass mixtures in terms of sward composition; among them, Dunavin (1992) and Jaramillo et al (2018) performed trials in Florida and evaluated the sward responses for 8 and 3 yr, respectively.…”
Section: Botanical Compositionsupporting
confidence: 90%
“…Williams et al (2004) reported improvement in average daily gain of Romosinuano (Bos taurus L.) calves in a creep feeding system where calves had access to RP. Management practices adopted during RP planting , in the establishment year (Castillo et al, 2013a(Castillo et al, , 2013b, and the entries used affect the performance of the pasture over time ( Jaramillo et al, 2018). In one of the few works performed, Dunavin (1992) evaluated the association of 'Florigraze' RP with 'Pensacola' bahiagrass.…”
Section: Herbage Responses and Biological N 2 Fixation Of Bahiagrass mentioning
confidence: 99%
See 3 more Smart Citations